Dynamic changes in the frequency and architecture of plasmodesmata during the sink-source transition in tobacco leaves - Sauer, Norbert; et al. (Protoplasma, 2001)
The sink-source transition in tobacco leaves was studied noninvasively using transgenic plants expressing the green-fluorescent protein (GFP) under control of the Arabidopsis thaliana SUC2 promoter, and also by imaging transgenic plants that constitutively expressed a tobacco mosaic virus movement protein (MP) fused to GFP MP-GFP. The sink-source transition was measured on intact leaves and progressed basipetally at rates of up to 600 mum/h. The transition was most rapid on the largest sink leaves. However, leaf size was a poor indicator of the current position of the sink-source transition. A quantitative study of plasmodesmatal frequencies revealed the loss of enormous numbers of simple plasmodemata during the sink-source transition. In contrast, branched plasmodesmata increased in frequency during the sink-source transition, particularly between periclinal cell walls of the spongy mesophyll. The progression of plasmodesmal branching, as mapped by the labelling of plasmodesmata with MP-GFP fusion, occurred asynchronously in different cell layers, commencing in trichomes and appearing lastly in periclinal cell wails of the palisade layer. It appears that dividing cells retain simple plasmodesmata for longer periods than nondividing cells. The rapid conversion of simple to branched plasmodesmata is discussed in relation to the capacity for macromolecular trafficking in developing leaf tissues.
Keywords: plasmodesmatal architecture; plasmodesmatal frequency; sink-source transition; green-fluorescent protein; tobacco; viral movement protein